Violent victimization of youth from a cross-national perspective: an analysis inspired by routine activity theory - Podaná, Zuzana (International review of victimology, 2017)
The article analyses cross-national variation in violent victimization of youth using data from the second sweep of the International Self-Report Delinquency Study. A multi-level approach is applied which takes into account individual factors as well as the characteristics of the immediate neighbourhood and the context of the given country. The routine activity theory suggested by Cohen and Felson is utilized to derive hypotheses about macro-level factors with the potential to explain differences in violent victimization rates. Specifically, the effects of homicide rates, the Gini coefficient, and the Human Development Index are analysed. The results reveal that the variation in violent victimization rates across countries is only partly attributable to the countries’ heterogeneity with respect to individual characteristics and lifestyle choices of youth, together with neighbourhood features. Furthermore, a significant effect is observed for a country’s Human Development Index, which relates higher levels of development to lower victimization risk, even when individual and neighbourhood characteristics are controlled for.